Elastic contact analysis of functionally graded brake disks subjected to thermal and mechanical loads - Sichani, Mohammadmehdi Shahzamanian; Sahari, Barkawi; Bayat, Mehdi; Mustapha, Faizal; Zahari, Nur Ismarrubie (Taylor & Francis, 2013)
In this paper, finite element contact analysis of a functionally graded (FG) brake disk in contact with a pad, subjected to rotation, contact pressure, and frictional heat, is presented. The material properties vary through the thickness according to a power-law characterized by a grading index, n. The contact surfaces are full-ceramic with full-metal free surface. The effects of n on the displacement, contact status, strain and stress are investigated. From the analysis, thermo-elastic and contact results are extremely dependent on n. Hence, n is an important criteria for the design of FG brake disks for automotive and aircraft applications.